Hurricanes and the Harvesting Decisions - Fritz Roka; Robert Rouse; Steve Futch; Ron Muraro (EDIS)
This paper addresses the generic question of whether a crop should be harvested after sustaining significant loss. This paper provides a citrus grower with a roadmap to determine the economic criteria for harvesting the remaining crop. Conversely, when is it in the best economic interest for a grower to abandon the remaining crop? While the hurricanes of 2004 motivated this paper, the analysis is applicable to any situation arising from natural disasters, pest infestations, or collapsing market prices.This paper addresses the generic question of whether a crop should be harvested after sustaining significant loss. This paper provides a citrus grower with a roadmap to determine the economic criteria for harvesting the remaining crop. Conversely, when is it in the best economic interest for a grower to abandon the remaining crop? While the hurricanes of 2004 motivated this paper, the analysis is applicable to any situation arising from natural disasters, pest infestations, or collapsing market prices. This document is FE624, a publication of the Food and Resource Economics Department, UF/IFAS Extension. Published March 2006.